2022
DOI: 10.1155/2022/9324471
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends and Hotspots of Q Fever Research: A Bibliometric Analysis 1990-2019

Abstract: Q fever is a worldwide distributed zoonosis caused by Coxiella burnetii, a Gram-negative bacterium. Despite existence of large amount of research data on the developments related to Q fever, no bibliometric analysis of this subject is available to our knowledge. Bibliometric studies are an essential resource to track scholarly trends and research output in a subject. This study is aimed at reporting a bibliometric analysis of publications related to Q fever (2,840 articles published in the period 1990-2019) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Most of the studies were conducted in Iran, Egypt, and Saudi Arabia, respectively and more than half of which were in the past five years. The results of a review on hotspots of Q fever research from 1990-2019, represented that Iran had a TP (total number of publications) of 46 (ranked 15th) and was a member of productive countries with 11 articles in 2019 27 .…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…Most of the studies were conducted in Iran, Egypt, and Saudi Arabia, respectively and more than half of which were in the past five years. The results of a review on hotspots of Q fever research from 1990-2019, represented that Iran had a TP (total number of publications) of 46 (ranked 15th) and was a member of productive countries with 11 articles in 2019 27 .…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…Chrcanovic had the greatest publication potential with a j of 24 followed by Tecco, Serra‐Negra and Ommerborn with a j of 20, 28 and 14, respectively. The location on the graph along with one of the curves or along a line from the origin represents different families of author publication potential or publication characteristics, respectively 25 …”
Section: Resultsmentioning
confidence: 99%
“…Ho′s group firstly proposed the ‘front page’ as a filter including the article title, abstract and author keywords 21 . This filter can avoid introducing unrelated publications for bibliometric analysis, since it was reported that big differences occurred when using the ‘front page’ as a filter in bibliometric research topics published in medical‐related journals in SCI‐EXPANDED, for example, Chinese Medical Journal , 22 World Neurosurgery , 23 Annals of Translational Medicine , 24 and BioMed Research International 25 …”
Section: Methodsmentioning
confidence: 99%
“…The "front page" filter can avoid introducing unrelated publications for bibliometric analysis. In recent years, a significant difference was found in a wide range of bibliometric studies using the "front page" as a filter, for example, research topics: Fenton oxidation for soil and water remediation (Usman & Ho, 2020), insomnia (Jallow et al, 2020), Q fever (Farooq et al, 2022), and temporomandibular disorders (Al-Moraissi et al, 2023).…”
Section: Data Sources and Methodsmentioning
confidence: 99%